Human adenoviruses associated with respiratory illness in neonates, infants, and children in the Sousse area of Tunisia. Issue 12 (13th August 2020) - Brini, Ines; Guerrero, Aida; Ezzine, Issaad‐Kawther; Orth‐Höller, Dorothea; Hetzer, Benjamin; Würzner, Reinhard; Hazgui, Olfa; Handous, Imene; Nouri‐Merchaoui, Sonia; Bouguila, Jihene; Mahdhaoui, Nabiha; Boughamoura, Lamia; et al.
Abstract: Background: The human Adenovirus (HAdV) is a common agent of acute respiratory infections (ARIs). Its clinical impact in immunocompetent children and in the context of coinfections remains unclear in Tunisia. Material and methods: HAdV‐ARIs were studied in hospitalized patients from birth to the age of 5 years from 2013 to 2014. Clinical and demographic characteristics, coinfections, and molecular characterization of HAdV were established. Results: HAdV‐positivity was detected in 114/583 specimens (19.6%) including 6.1% single infections and 93.9% coinfections. Adenoviral coinfections mostly comprised human Rhinovirus (50.9%), Streptococcus pneumoniae (34.2%), human Respiratory Syncytial virus A/B (29.8%), and human Coronaviruses (21.9%). HAdV infection was predominant in the pediatric population (25.0% vs 10.0% in neonates, P  < .001) and peaked in February 2014 (21.1%). HAdV severity of pediatric cases is characterized by low saturation of oxygen (<94%, 33.8%, P  = .05) and long duration of oxygen support (≥5 days, 32.7%, P  = .02). Severe HAdV infections were described with S. pneumoniae coinfection, which seemed to increase the risk of death. HAdV genotyping identified HAdV‐C as the most common species. Severe ARIs were observed in all HAdV‐identified types. Phylogenetic analysis revealed that sequences were variable suggesting the circulation of different HAdV strains sharing more similarities to strains circulating in Europe or Asia than those from Africa. Conclusion: This first molecular study of HAdV in Tunisia demonstrated that it has an important role in severe ARIs with HAdV‐C being the most common species. S. pneumoniae codetection seems to increase the severity of HAdV‐ARIs.